Children with Learning Problems: Academic History, Academic Prediction, and Adjustment Three Years After Assessment. - Hinton, George G.; Knights, Robert M. (Exceptional Children, 1971)
This study is a 3 year followup of 67 children who were referred for learning problems at school. Their academic progress is described and a high failure rate noted. A multiple regression analysis of the initial scores on a neuropsychology test battery illustrates the importance of verbal abilities for successful grade advancement. Management with parental counseling and medication resulted in a reported improvement of 75 percent of the children.